Pesticide Exposure Assessment Paradigm for Solitary Bees. Issue 1 (3rd December 2018) - Sgolastra, Fabio; Hinarejos, Silvia; Pitts-Singer, Theresa L; Boyle, Natalie K; Joseph, Timothy; Lūckmann, Johannes; Raine, Nigel E; Singh, Rajwinder; Williams, Neal M; Bosch, Jordi
Abstract: Current pesticide risk assessment for bees relies on a single (social) species, the western honey bee, Apis mellifera L. (Hymenoptera: Apidae). However, most of the >20, 000 bee species worldwide are solitary. Differences in life history traits between solitary bees (SB) and honey bees (HB) are likely to determine differences in routes and levels of pesticide exposure. The objectives of this review are to: 1) compare SB and HB life history traits relevant for risk assessment; 2) summarize current knowledge about levels of pesticide exposure for SB and HB; 3) identify knowledge gaps and research needs; 4) evaluate whether current HB risk assessment schemes cover routes and levels of exposure of SB; and 5) identify potential SB model species for risk assessment. Most SB exposure routes seem well covered by current HB risk assessment schemes. Exceptions to this are exposure routes related to nesting substrates and nesting materials used by SB. Exposure via soil is of particular concern because most SB species nest underground. Six SB species ( Hymenoptera: Megachilidae - Osmia bicornis L., O. cornifrons Radoszkowski, O. cornuta Latreille, O. lignaria Say, Megachile rotundata F., and Halictidae - Nomia melanderi Cockerell) are commercially available and could be used in risk assessment. Of these, only N. melanderi nests underground, and the rest are cavity-nesters. However, the three Osmia species collect soil to build their nests. Life history traits of cavity-nesting species make them particularly suitable for semifield and, to a lesser extent, field tests. Future studies should address basic biology, rearing methods and levels of exposure of ground-nesting SB species.